Media as a Factor of Intellectual Evolution - Ashvanyan, Sargis; Ravochkin, Nikita (Bulletin of Yerevan University G: Economics, 2025)
The article presents the philosophical media, which act as a factor of intellectual evolution in the realities of modern social development. The authors consider media and technization in relation to the formation of new principles of social existence. The specificity of intellectualization of social systems is revealed. Innovative effects of media influencing society for the life of individual and collective subjects are determined. A comparative analysis of the implementation of intellectual achievements in practice is given. The possibilities of cognitive, value and behavioral resources in relation to the consolidation of society are clarified. The authors substantiate the popularity of media as an open communication system. Emphasis is placed on the pragmatics of media. The authors consider new media from the standpoint of challenges for the formation of new principles of social existence. The instrumental capabilities of media in the field of journalism are identified. The innovative effect of storytelling for intellectual evolution is determined. The positive potential of immersive media and VR technologies is designated. The possibilities of narratives in relation to the foundations of personal and collective existence are clarified. The emphasis is placed on the pragmatics of media. In conclusion, the article summarizes and summarizes the results of the study.